Competitive Debate: A Successful Inter-team Gamification Experience in the Human Resources Subject - Sánchez Prieto, Guillermo A.; Martín Rodrigo, María José; Rua Vieites, Antonio (Frontiers in Psychology, 2021)
Students demand more active and participating teaching innovation methods and activities such as presentations are not enough to satisfy those demands. In this research competitive debate is used as gamification with third year students from a Business School at the Human Resources Management subject. Out of this experience qualitative and quantitative data are obtained. Results reinforce keeping on with classroom competitive debate due to the evidence of its motivational, learning, communication skills improvement and knowledge acquisition effects. The possibility of application with actual professionals is seriously considered.